The emergence of procyclical fertility: The role of breadwinner women - Coskun Dalgic, Sena; Dalgic, Husnu C. (Journal of Monetary Economics, 2024)
Fertility in the US exhibits an increasingly more procyclical pattern. We argue that women's breadwinner status is behind procyclical and lower fertility: (i) women's relative income in the family has increased over time; and (ii) women are more likely to work in relatively stable and countercyclical industries whereas men tend to work in volatile and procyclical industries. This creates a countercyclical gender income gap as women become breadwinners in recessions, producing an insurance effect of women's income. Our quantitative framework shows that rising breadwinner status of women can explain both the emergence of procyclical fertility and the decline in fertility rate in the second half of the 20th century.
Created from Fastlane, Scopus look-up
Keywords: Fertility; Gender gap; Industry cyclicality; Procyclical fertility; Quality-quantity trade-off